2012
DOI: 10.1021/jz301182a
|View full text |Cite
|
Sign up to set email alerts
|

Improved CO Adsorption Energies, Site Preferences, and Surface Formation Energies from a Meta-Generalized Gradient Approximation Exchange–Correlation Functional, M06-L

Abstract: A notorious failing of approximate exchange-correlation functionals when applied to problems involving catalysis has been the inability of most local functionals to predict the correct adsorption site for CO on metal surfaces or to simultaneously predict accurate surface formation energies and adsorption energies for transition metals. By adding the kinetic energy density τ to the density functional, the revTPSS density functional was shown recently to achieve a balanced description of surface energies and ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 39 publications
16
64
0
Order By: Relevance
“…We have confirmed the adequacy of these approaches in the past for two difficult systems, e.g. CO adsorption on MgO(100) 58 and CO and NO adsorption on Nidoped MgO(100), 59 which are also corroborated by the quite encouraging results from recent works concerning the interaction of CO with the (111) surfaces of Rh, Pt, Cu, Ag and Pd 106 or the interaction of benzene, pyridine, thymine and cytosine with Au (111), 107 where the M06-L method and a periodic model approach were used. Another very hot topic where DFT approaches including van der Waals corrections are being used is in the study of the interaction of graphene with adsorbates 70,77,[97][98][99]108 or with a substrate.…”
Section: Molecular Adsorptionsupporting
confidence: 85%
“…We have confirmed the adequacy of these approaches in the past for two difficult systems, e.g. CO adsorption on MgO(100) 58 and CO and NO adsorption on Nidoped MgO(100), 59 which are also corroborated by the quite encouraging results from recent works concerning the interaction of CO with the (111) surfaces of Rh, Pt, Cu, Ag and Pd 106 or the interaction of benzene, pyridine, thymine and cytosine with Au (111), 107 where the M06-L method and a periodic model approach were used. Another very hot topic where DFT approaches including van der Waals corrections are being used is in the study of the interaction of graphene with adsorbates 70,77,[97][98][99]108 or with a substrate.…”
Section: Molecular Adsorptionsupporting
confidence: 85%
“…The M06-L functional is used in this work since in a recent comparative study on the performance of nine different DFT functionals to calculate the interaction enthalpy of methane with a cluster model of Na-ETS-10, the M06-L approach was found to provide the best results [21].Besides,the M06-L approach together with a cluster model was found to provide very accurate energetic, vibrational and structural information for some other difficult systems such as i) adsorption of CO on MgO(001) [30], ii) the adsorption of CO and NO on Ni-doped MgO(001) [31], and iii) the interaction of water with open metal sites of CuBTC [32]. Very encouragingly, recent works concerning the interaction of CO with the (111) surfaces of Rh, Pt, Cu, Ag and Pd [33] or the interaction of benzene, pyridine, thymine and cytosine with Au(111) [34]showed that the M06-L method is suitable for treating dispersion dominated interactionsof adsorbateswith metallic surfaces [35].The M06-L approach was also effectively employed to predict reaction energies in organometallic systems [36][37][38] and the benchmark study on the interaction of hydrocarbons and smaller gases with several zeolite clusters byZhao and Truhlar [39]shows that the M06 family of functionals is well suited to study this kind of systems.Additionally, in our very recent work on the interaction of five atmospheric gases with Na-ETS-10 [21], calculated enthalpic data for methane, nitrogen and, at some extent, carbon dioxide, and calculated vibrational data for methane, nitrogen, hydrogen, carbon dioxide and water were found to be in very satisfactory agreement with experimental isosteric heats [40,41] and infrared results [42][43][44][45], respectively. The same 2Ti cluster model used in Ref.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In solid-state physics, the prediction of the fundamental (band) gap is an intrinsic limitation of explicit density-dependent semilocal functionals [7,8]. In material science, the proper description of charge localization and charge distributions between subsystems is a major challenge [9,10] that affects many problems, e.g., surface adsorption [11,12]. In molecular physics and chemistry, missing field-counteracting terms have serious, detrimental consequences for the calculation of polarizabilities, hyperpolarizabilities, and charge transfer [13][14][15].…”
Section: Introductionmentioning
confidence: 99%